Developing master's level education students as researchers: mentors' and mentees' experiences. Issue 2 (15th March 2022) - Ferguson, Therese; Ellis, Tanneice
ABSTRACT: Mentoring within higher education develops capacity of early-career academic staff and doctoral students. For students in taught Master's degree programs who may not envision themselves moving on to doctoral studies, research competencies are still needed as they include transferable skills and enable professionals to undertake research within their contexts. Those working within educational settings, for instance, can carry out action research to address issues within their institutions.. This generic qualitative study explored the experiences of mentors and mentees in relation to researcher development of graduate research students in education at a Caribbean university. The study found that mentoring relationships enhanced students' research capabilities, resulted in students identifying themselves as researchers, and enabled those working within the education sector to translate these research skills into their professional contexts. The findings of the research are useful with respect to fostering a culture of mentorship among academic staff within the discipline of education.